DistributiveProperty<br />4(x + 3) = 4x + 12<br />Factoring<br />4x + 12 = 4(x + 3) <br />GCF of 4x and 12<br />
Factor<br />GCF of 10y and 25<br />10y = 2 · 5 · y<br />  25 = 5 · 5<br />GCF =    5<br />Factor 10y – 25<br />	= 5(2y – 5...
     3x2y = 3·x·x·y<br />12xy2 = 2·2·3·x·y·y <br />Factor<br />= 3xy (x + 4y)<br />GCF:   3xy<br />
Factor<br />GCF:<br />Example 2-1a<br />
( 7 )( 0 ) = 0<br />( 51 )( 0 )= 0<br />( 0 )( 31 ) = 0<br />( 79 )( 0 ) = 0<br />( 42 )( 0 ) = 0<br />( 0 )( 0 ) = 0<br />
Solve:  (x + 1)(x – 2) = 0<br />  x + 1 = 0    or    x – 2 = 0      - 1  - 1             + 2     +2<br />        x = -1   ...
Solve:  (x + 3)(x – 5) = 0<br />  x + 3 = 0    or    x – 5 = 0      - 3  - 3             + 5     +5<br />        x = -3   ...
Solve		<br />or<br />+2    +2<br />+1    +1<br />4      4<br />Example 2-4a<br />
Solve: x2 – 4x = 12<br />	x2 – 4x – 12 = 0<br />-12     -12<br />Solve:  (x + 2)(x – 6) = 0<br />  x + 2 = 0    or    x – ...
Solve<br />-12y2     -12y2<br />or<br />4       4<br />-1               -1<br />-3y = -1<br />-3       -3<br />
Upcoming SlideShare
Loading in …5
×

Alg1 lesson 9-2

276 views
257 views

Published on

Published in: Education, Technology
0 Comments
0 Likes
Statistics
Notes
  • Be the first to comment

  • Be the first to like this

No Downloads
Views
Total views
276
On SlideShare
0
From Embeds
0
Number of Embeds
0
Actions
Shares
0
Downloads
0
Comments
0
Likes
0
Embeds 0
No embeds

No notes for slide

Alg1 lesson 9-2

  1. 1. DistributiveProperty<br />4(x + 3) = 4x + 12<br />Factoring<br />4x + 12 = 4(x + 3) <br />GCF of 4x and 12<br />
  2. 2. Factor<br />GCF of 10y and 25<br />10y = 2 · 5 · y<br /> 25 = 5 · 5<br />GCF = 5<br />Factor 10y – 25<br /> = 5(2y – 5) <br />GCF:<br />Example 2-1a<br />
  3. 3. 3x2y = 3·x·x·y<br />12xy2 = 2·2·3·x·y·y <br />Factor<br />= 3xy (x + 4y)<br />GCF: 3xy<br />
  4. 4. Factor<br />GCF:<br />Example 2-1a<br />
  5. 5. ( 7 )( 0 ) = 0<br />( 51 )( 0 )= 0<br />( 0 )( 31 ) = 0<br />( 79 )( 0 ) = 0<br />( 42 )( 0 ) = 0<br />( 0 )( 0 ) = 0<br />
  6. 6. Solve: (x + 1)(x – 2) = 0<br /> x + 1 = 0 or x – 2 = 0 - 1 - 1 + 2 +2<br /> x = -1 or x = 2<br />Check 2:<br />(x + 1)(x – 2) = 0<br />(2 + 1)(2 – 2) = 0<br />(3)(0) = 0 <br />Check -1:<br />(x + 1)(x – 2) = 0<br />(-1 + 1)(-1 – 2) = 0<br />(0)(-3) = 0 <br />
  7. 7. Solve: (x + 3)(x – 5) = 0<br /> x + 3 = 0 or x – 5 = 0 - 3 - 3 + 5 +5<br /> x = -3 or x = 5<br />
  8. 8. Solve <br />or<br />+2 +2<br />+1 +1<br />4 4<br />Example 2-4a<br />
  9. 9. Solve: x2 – 4x = 12<br /> x2 – 4x – 12 = 0<br />-12 -12<br />Solve: (x + 2)(x – 6) = 0<br /> x + 2 = 0 or x – 6 = 0 - 2 - 2 + 6 +6<br /> x = -2 or x = 6<br />
  10. 10. Solve<br />-12y2 -12y2<br />or<br />4 4<br />-1 -1<br />-3y = -1<br />-3 -3<br />

×